Sustainable Regional Revenue and Capital Expenditure Management Strategies in Improving Financial Performance and Economic Growth in Tabalong Regency - Setiasih, Endang Try; Maryani, Dedeh; Asri, Jatnika Dwi; Zulaikha, Siti; Maemunah, Cucu (International Journal Labs, 2025)
The implementation of regional autonomy in Indonesia has heightened the necessity for local governments to optimize their financial resources to foster economic growth and enhance public welfare. However, many regions, including Tabalong Regency, continue to face significant challenges in achieving fiscal sustainability and effectively translating financial capacity into tangible development outcomes. The purpose of this research is to analyze internal and external factors that affect financial performance, as well as identify the right strategies to implement. The method used was qualitative with SWOT analysis, which involved collecting secondary data from regional financial statements and interviews with key informants. The results showed that internal strengths included strong leadership support and legislative-executive synergy, while weaknesses related to the quality of human resources and delayed budget absorption. External opportunities include buffer zones for IKN and digital innovation, while threats include rapid regulatory changes and global economic crises. This study recommends human resource development and improvement of capital expenditure processes as strategic steps to achieve better regional financial goals.